2015
DOI: 10.1177/009164711504300306
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Evidence-Based Practices into Faith-Based Organization Service Programs

Abstract: Faith-based organizations (FBOs) are increasingly involved in providing a range of services in communities and research indicates that such involvement will increase in the future. However, like other types of organizations, FBOs generally have been slow to embrace evidence-based practices (EBPs)-those that have scientific evidence of being beneficial. We contend that incorporating EBPs into both new and existing FBOs' service programs can enhance their effectiveness. In this paper, we discuss several relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Being part of a small group has the potential to provide members a variety of coping resources. Thus, there is a ready-made infrastructure in many churches for disseminating psychological knowledge and interventions (Savage, 2003; Terry et al, 2015).…”
Section: Church Ministry and Mental Healthmentioning
confidence: 99%
“…Being part of a small group has the potential to provide members a variety of coping resources. Thus, there is a ready-made infrastructure in many churches for disseminating psychological knowledge and interventions (Savage, 2003; Terry et al, 2015).…”
Section: Church Ministry and Mental Healthmentioning
confidence: 99%
“…Relationships between outputs and outcomes are not as clear because they are not directly observed or easily understood." 25 Recognizing the connection between outputs and outcomes is one of the biggest challenges for mission organizations. Basing ministry assessments upon quantitative data alone reveals only a portion of the evidence needed.…”
Section: Attaining Desired Outcomes and Avoiding Unintended Consequencesmentioning
confidence: 99%
“…Traditionally, African American churches provide spiritual nurturing, leadership, and health promotion activities for its congregants and members of the community [12]. Studies have identified that successful implementation of faith-based health programs are linked to the support of pastors and key stakeholders in FBO [23][24][25]. African American Churches are a source of strength, leadership, and support for the community that often provides educational programs, which help individuals make lifestyle and health changes [12,23].…”
Section: Impact Of Faith-based Organizations On Help Seeking Behaviorsmentioning
confidence: 99%